2017
DOI: 10.3892/etm.2017.4218
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 regulates apoptosis in human lung adenocarcinoma A549 cells via endoplasmic reticulum stress and mitochondrial signaling pathways

Abstract: Abstract. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a member of the subtilisin family of PCs that encodes a neural apoptosis-regulated convertase 1. However, the precise role of PCSK9 in lung cancer cell apoptosis has remained elusive. In the present study, A549 human lung adenocarcinoma cells were transfected with PCSK9 small interfering (si)RNA to investigate the underlying mechanisms of apoptosis. The results indicated that PCSK9 siRNA exhibited anti-tumor activity by inducing apoptosis as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…Little functional information on this protein is available, although it is ubiquitously expressed in at least 25 tissues 33 . The other gene is proprotein convertase subtilisin/kexin type 9 (PCSK9), primarily involved in lipid homeostasis and apoptosis 34 . PCSK9 is thought to have two major functions: (1) maintenance of lipid homeostasis by the regulation of low-density lipoprotein receptors and (2) the regulation of neural apoptosis 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little functional information on this protein is available, although it is ubiquitously expressed in at least 25 tissues 33 . The other gene is proprotein convertase subtilisin/kexin type 9 (PCSK9), primarily involved in lipid homeostasis and apoptosis 34 . PCSK9 is thought to have two major functions: (1) maintenance of lipid homeostasis by the regulation of low-density lipoprotein receptors and (2) the regulation of neural apoptosis 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The other gene is proprotein convertase subtilisin/kexin type 9 (PCSK9), primarily involved in lipid homeostasis and apoptosis 34 . PCSK9 is thought to have two major functions: (1) maintenance of lipid homeostasis by the regulation of low-density lipoprotein receptors and (2) the regulation of neural apoptosis 34 . In general, the overexpression or upregulation of PCSK9 is associated with the dysregulation of pathways involved in the cell cycle, inflammation and apoptosis while the inhibition or downregulation of PCSK9 in carcinogenic lung cells has been associated with apoptosis of these cell lines 34 .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that PCSK9 is related to various biological pathways, such as the in ammatory response, immune response, metabolism, cell cycle and apoptosis [20][21][22], suggesting that PCSK9 is a multifunctional protein. However, only a few studies have reported the relationship between PCSK9 and cancer [6,8]. One study on HCC reported a decrease in PCSK9 expression in human HCC tissues but did not clarify the speci c signi cance of low PCSK9 expression levels in the carcinogenesis and development of HCC [4].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PCSK9 has been found to be closely related to the occurrence and development of a variety of tumors, including melanoma, prostate cancer, and lung cancer. [6][7][8] However, the concrete role of PCSK9 and its relationship with HCC development is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies highlight the involvement of PCSK9 in imparting advantages to certain cancer types. PCSK9, also known as neural apoptosis-regulated convertase 1 (NARC1), exhibits an anti-apoptotic function in lung cancer and neuroglioma cells [ 5 , 6 ]. It is demonstrated to be involved in metastasis such that its deficiency reduces melanoma metastasis due to lower circulatory cholesterol level [ 7 ].…”
Section: Introductionmentioning
confidence: 99%